Pengaruh Nilai CBR Tanah Bermasalah Yang Distabilisasi Dengan Fly ash di Wilayah Perbatasan Provinsi Kaltara - Fuad Harwadi; Hasrullah Hasrullah; Rachel Zandra Singal (Borneo Engineering : Jurnal Teknik Sipil, 2022)
In construction problem soils are often encountered, as well as in the border area of North Kalimantan Province, there are problematic soils such as peat soil and expansive soil. Problematic soils have low bearing capacity and high compressibility, therefore it is necessary to make improvements in problematic soils. One of the soil improvements whose application is quite easy and relatively inexpensive to implement is stabilization. This research uses coal waste material (fly ash) as a stabilizer from PLTU Sekayan in Apung village, Kaltara Province. The purpose of this study was to obtain changes in the CBR parameters on peat soil and expansive soil by mixing fly ash with variations in the addition of fly ash by 20%, 40%, and 60%, and through curing for 20, 30, 40, and 60 days. The analysis is presented in graphical form by comparing the original soil that has not been stabilized and the soil that has been stabilized with fly ash. From this research, it was found that the addition of a stabilizing agent in the form of fly ash can increase the CBR value in problematic soils. In the expansive soil CBR test in the laboratory, there was a very large increase in the CBR value, namely from the initial condition of 2,65% to 33.7% with the addition of 60% fly ash and a curing period of 60 days. On peat soil, the initial CBR value was 0,79% to 9.8% with the addition of 60% fly ash and a curing period of 60 days.